Táxons supraespecíficos (subfamília e gênero) como alternativa para a estimação da riqueza de espécies de formigas (hymenoptera- formicidae) em diferentes Estados sucessionais da floresta e sistemas agroflorestais, na Amazônia Oriental, Brasil. - Gutiérrez, Jhonatan Andrés Muñoz (2016)
Higher taxa (subfamily and genus) of ants as surrogates of species richness in a chronosequence of fallows, old-growth forests and agroforestry systems in the Eastern Amazon. Amazon deforestation is one of the main causes of biodiversity losses worldwide. Ants are key ecosystem engineers; therefore, ant diversity loss may indicate loss of crucial ecosystem functions. The aim of this study was to evaluate soil ant’s richness and to estimate if higher taxa levels (Subfamily and Genus) can be used as surrogates of species richness in different vegetation types (fallows, old-growth forests and agroforestry systems) in Eastern Amazon. We sampled 65 areas in the Maranhão and Pará States during the years of 2011-2014. The sampling scheme followed the procedure of Tropical Soil Biology and Fertility (TSBF). We first characterized all the vegetation types according to their age and estimated species richness. To evaluate if higher taxa can be used as surrogates we used linear regressions. In total, we collected 180 species distributed in 60 genera. The results showed that ant species richness was higher in intermediate fallows (88) and old secondary forest (76), and was lower in agroforestry systems (38) and mature riparian forest (35). The genus level was the best surrogate to estimate the ant’s species richness across the different vegetation types and explained 72-97 % (P < 0.001) of the total species variability. Our results confirmed that the genus level is an excellent surrogate to estimate the ant’s species richness in the region and that both fallows and agroforestry systems may contribute in the conservation of Eastern Amazon ant community.